Fecobionics: A Novel Bionics Device for Studying Defecation - Sun, Daming; Huang, Zhiyong; Zhuang, Zhuoli; Ma, Zhiyao; Man, Lo Kar; Liao, Donghua; Gregersen, Hans (Annals of biomedical engineering, 2019)
During defecation, solid, semisolid or liquid stools are eliminated via the anus in a complex physiological process. Up to 25% of the population are affected by anorectal disorders that are poorly recognized and treated. We developed a new bionics device, a simulated stool named Fecobionics, to replace several current tests of anorectal function. Fecobionics was developed to simulate the defecation process that depends on rectal forces, the anorectal size angle, and anorectal size and sensitivity. Fecobionics provided axial pressure signatures, measurement of bending (anorectal angle) and geometric mapping in a single examination. It had the consistency and shape of normal stool. The device had a soft core with embedded electronics and a bag for distension. The paper describes the device development and validation. Furthermore, data were obtained in preliminary experiments in pigs, healthy human subjects and patients with focus on four important features of the system, i.e. measurements of pressure signatures, bending characteristics, impedance measurements and data transmission. Accurate pressure and orientation data as well as geometric profiles were successfully obtained on the bench as well as in vivo in pigs and human subjects during defecation. Fecobionics is a novel technology imitating defecation. The clinical future ultimately depends on its ability to impact on daily treatment of anorectal disorders. A potential long-term clinical application is use of the device for biofeedback training for dyssynergic defecation.